The OCareCloudS project: Toward organizing care through trusted cloud services. (2nd April 2016) - De Backere, Femke; Ongenae, Femke; Vannieuwenborg, Frederic; Van Ooteghem, Jan; Duysburgh, Pieter; Jansen, Arne; Hoebeke, Jeroen; Wuyts, Kim; Rossey, Jen; Van den Abeele, Floris; Willems, Karen; Decancq, Jasmien; et al.
Abstract : The increasing elderly population and the shift from acute to chronic illness makes it difficult to care for people in hospitals and rest homes. Moreover, elderly people, if given a choice, want to stay at home as long as possible. In this article, the methodologies to develop a cloud-based semantic system, offering valuable information and knowledge-based services, are presented. The information and services are related to the different personal living hemispheres of the patient, namely the daily care-related needs, the social needs and the daily life assistance. Ontologies are used to facilitate the integration, analysis, aggregation and efficient use of all the available data in the cloud. By using an interdisciplinary research approach, where user researchers, (ontology) engineers, researchers and domain stakeholders are at the forefront, a platform can be developed of great added value for the patients that want to grow old in their own home and for their caregivers.